Truth, meaning, reality - Horwich, Paul. (Oxford : Clarendon Press, 2010)
'Truth, Meaning, Reality' presents a broad and unified deflationism that encompasses language, thought, knowledge and reality. Horwich's story begins with his minimalist view of truth which paves the way to an account of meaning as use. The 14 essays constitute a coherent and complete expression of this philosophy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth; Meaning (Philosophy); Reality; Philosophy of mind; Metaphysics; Knowledge, Theory of